Environment-friendly laminated piece and packaging material comprising same
By using laminates with high biocarbon content paper layers and polyhydroxyalkanoate film layers, the problem of difficult decomposition and insufficient barrier properties of existing packaging materials in the ocean and soil is solved, and high recyclability and Excellent gas barrier and sealing properties, suitable for a variety of packaging applications.
Patent Information
- Application Number
- CN202380044059.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-09
- Filing Date
- 2023-06-28
- Publication Date
- 2025-01-10
AI Technical Summary
Existing packaging materials are difficult to decompose in the ocean and soil, and lack excellent oxygen and moisture barrier properties, limiting their recyclability and environmental protection.
A laminate consisting of a paper layer with a biocarbon content of 85% or more and a polyhydroxyalkanoate (PHA) film layer with a thickness of 8 μm to 70 μm, combined with biodegradable materials such as polylactic acid and thermoplastic starch to form a biodegradable material with Packaging material with excellent gas barrier properties and sealing properties.
It achieves efficient decomposition in the ocean and soil, while providing excellent oxygen and moisture barrier and sealing, improving the recyclability and environmental protection of packaging materials, and is suitable for long-term and short-term packaging needs.
Smart Images

Figure CN119300984A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an environmentally friendly laminate which has excellent environmental properties because it is highly biodegradable in the ocean and soil, and has excellent oxygen / moisture barrier and sealing properties, and can be used as a packaging material in various fields. Background Art
[0002] Generally, in order to ensure the function as a packaging material, the packaging material is made by laminating a plurality of resin layers composed of petrochemical-based synthetic resins. However, due to the use of different petrochemical-based synthetic resins, the recyclability of the packaging material becomes poor, and their individual handling is limited. In addition, since an aluminum foil or an aluminum-deposited resin layer is used to increase the barrier property to oxygen and / or moisture, it is almost impossible to handle the packaging material individually.
[0003] In order to solve this problem, a packaging material made of paper and biodegradable raw materials has been proposed. However, these packaging materials have a problem in that the raw materials can only be decomposed under specific conditions. In addition, in order to increase the barrier properties to oxygen and / or moisture, packaging materials have been manufactured by coating metal materials (not aluminum) or introducing barrier materials (such as EVOH, PVA and PVDC). Since they cannot be well decomposed in the ocean and soil, this cannot be a fundamental countermeasure to solve the separate treatment and marine pollution caused by plastics.
[0004] Therefore, in order to improve the recyclability and marine biodegradability of packaging materials, paper packaging materials combining paper and biodegradable films are being developed. However, the paper packaging materials developed so far do not significantly improve recyclability because the content of biodegradable films is greater than that of paper. In addition, if the biodegradable film is not coated to ensure barrier properties to oxygen and moisture, its use as an industrial packaging material for food and cosmetics that require long-term storage is limited.
[0005] Therefore, there is a need to develop packaging materials with improved recyclability and enhanced performance while decomposing well in oceans and soils.
[0006] [Prior art literature]
[0007] [Patent Document]
[0008] (Patent Document 1) Korean Patent Publication No. 2021-0008466. Summary of the invention
[0009] Technical issues
[0010] The present invention aims to provide a laminate having excellent recyclability, decomposing well in the ocean and soil, and having excellent barrier properties to oxygen and / or moisture (gas barrier properties) and sealing properties.
[0011] Furthermore, the present invention is directed to a packaging material comprising the laminate.
[0012] Solution to the problem
[0013] According to one aspect of the present invention for achieving the above object, a laminate is provided, comprising a paper layer and a film layer, wherein the paper layer has a biochar content of 85% or more and a tensile strength of 8 MPa or more, and the film layer comprises polyhydroxyalkanoate (PHA) and has a thickness of 8 μm to 70 μm; the polyhydroxyalkanoate (PHA) is a homopolymer or copolymer of 3-hydroxypropionic acid (3HP), 4-hydroxybutyric acid (4HB), 3-hydroxyvalerate (3HV), 5-hydroxyvalerate (5HV), 3-hydroxyhexanoate (3HH), 6 -hydroxyhexanoate (6HH) and 3-hydroxyoctanoate (3HO) monomer repeating units; the copolymer comprises at least one repeating unit derived from a monomer selected from 3-hydroxybutyrate (3HB), 3-hydroxypropionic acid (3HP), 4-hydroxybutyrate (4HB), 3-hydroxyvalerate (3HV), 5-hydroxyvalerate (5HV), 3-hydroxyhexanoate (3HH), 6-hydroxyhexanoate (6HH) and 3-hydroxyoctanoate (3HO), the at least one repeating unit being present in an amount of 0.1 wt % to 50 wt %, and the thickness of the film layer is less than 75 wt % of the total thickness of the laminate.
[0014] In an embodiment, the polyhydroxyalkanoate (PHA) can be a copolymer comprising a first repeating unit and a second repeating unit, wherein the first repeating unit and the second repeating unit are respectively derived from a monomer selected from 3-hydroxybutyrate (3HB), 3-hydroxypropionic acid (3HP), 4-hydroxybutyrate (4HB), 3-hydroxyvalerate (3HV), 5-hydroxyvalerate (5HV), 3-hydroxyhexanoate (3HH), 6-hydroxyhexanoate (6HH) and 3-hydroxyoctanoate (3HO), and the first repeating unit and the second repeating unit are different from each other.
[0015] In another embodiment, the polyhydroxyalkanoate (PHA) may be a copolymer comprising 0.1 wt % to 50 wt % of the first repeating unit or the second repeating unit, based on the total weight of the polyhydroxyalkanoate (PHA).
[0016] In another embodiment, the polyhydroxyalkanoate (PHA) may be a copolymer comprising 50 to 99.9 wt % of a first repeating unit derived from 3-hydroxybutyrate (3HB) and 0.1 to 50 wt % of a second repeating unit derived from a monomer selected from 3-hydroxypropionic acid (3HP), 4-hydroxybutyrate (4HB), 3-hydroxyvalerate (3HV), 5-hydroxyvalerate (5HV), 3-hydroxyhexanoate (3HH), 6-hydroxyhexanoate (6HH) and 3-hydroxyoctanoate (3HO).
[0017] In another embodiment, the film layer may have a biochar content of 40% or more.
[0018] In another embodiment, the film layer may have a tensile strength of 5 MPa or more and a sealing strength of 0.5 kgf or more.
[0019] In another embodiment, the film layer may further include at least one selected from polylactic acid (PLA), polybutylene adipate terephthalate (PBAT), polybutylene succinate (PBS), thermoplastic starch (TPS), polyvinyl alcohol (PVA), polycaprolactone (PCL), bio-derived polyethylene and bio-derived polypropylene.
[0020] In another embodiment, the polyhydroxyalkanoate (PHA) may be a poly(3-hydroxybutyrate-co-4-hydroxybutyrate) copolymer.
[0021] In another embodiment, the polyhydroxyalkanoate (PHA) may have an average molecular weight of 30,000 to 1,000,000 g / mol.
[0022] In another embodiment, the paper layer may have a tensile strength of 8 MPa to 100 MPa, a tear strength of 20 gf to 600 gf, and a 2 Up to 350g / m 2 The basis weight.
[0023] In another embodiment, the laminate may have a peel strength of 200 gf or more.
[0024] In another embodiment, the laminate may have a total biochar content of 25% or more.
[0025] In another embodiment, the laminate may have a 2 ·Daily up to 1,200cc / m 2 ·Day oxygen transmission rate and 1g / m 2 ·Day to 150g / m 2Water vapor transmission rate of the day.
[0026] According to another aspect of the present invention, there is provided a packaging material comprising a laminate.
[0027] Advantageous Effects of the Invention
[0028] Since the laminate according to the present invention includes a paper layer and a film layer having optimized physical properties (e.g., tensile strength, tear strength, etc.) and a biochar content within a specific range, the laminate has high recyclability, is easily decomposed in the ocean and soil, and has excellent barrier properties to oxygen and / or moisture (gas barrier properties) and sealing properties even if it does not include a conventional barrier layer.
[0029] Therefore, the laminate according to the present invention can be advantageously used as a packaging material for food, medicine, cosmetics, and industrial products that maintain a packaged state for a long time, and a disposable packaging material that maintains a packaged state for a short time. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is a cross-sectional view showing a laminate according to an embodiment of the present invention.
[0031] Figure 2 is a cross-sectional view showing another laminate according to an embodiment of the present invention. DETAILED DESCRIPTION
[0032] Best Mode for Carrying Out the Invention
[0033] Hereinafter, the present invention will be described with reference to the embodiments. Herein, the present invention is not limited to the contents given below, and the present invention can be modified in various forms as long as the gist of the present invention is not changed.
[0034] In this specification, when it is mentioned that an element is formed, connected or combined on or under another element, it means all cases where one element is formed, connected or combined with another element directly or indirectly through another element. In addition, it should be understood that the standard of the top and bottom of each component can vary depending on the direction of viewing the object.
[0035] In this specification, the term "comprising" is intended to specify specific features, regions, steps, processes, elements and / or components. It does not exclude the existence or addition of any other features, regions, steps, processes, elements and / or components unless there is a clear description to the contrary.
[0036] Unless otherwise indicated, all numbers and expressions relating to amounts of components, reaction conditions, and so forth used herein are to be understood as modified by the term "about."
[0037] The present invention relates to a laminate and a packaging material comprising the same, wherein the laminate comprises a paper layer and a film layer having optimized physical properties and a biocarbon content within a specific range, which will be described in detail as follows.
[0038] Laminates
[0039] The laminate according to the present invention comprises a paper layer and a film layer, said paper layer and said film layer will be referred to as Figure 1 The detailed description is as follows.
[0040] Paper layer
[0041] The laminate (10) according to an embodiment of the present invention comprises a paper layer (11). The paper layer (11) serves as a base material for forming a film layer (12) and a printing layer in the laminate (10) while ensuring the mechanical strength of the laminate (10).
[0042] The paper layer (11) may be formed of a paper substrate (paper), and the paper substrate is made of mechanical pulp, semi-chemical pulp or chemical pulp. The paper substrate may specifically include at least one selected from white paper (imitation kraft paper), rice white paper, colored paper, rough paper, thick paper, pile paper, art paper, snowflake paper, snow-white paper, single-sided art paper, royal art paper, NCR paper, imitation leather paper, straight paper, CCP paper, kraft paper, manila ivory paper, royal ivory paper, tracing paper, patterned paper, fancy paper, cotton paper, label paper, whiteboard paper, photo paper and cup paper.
[0043] The paper layer (11) may have a biocarbon content (renewable carbon content (carbon ratio)) of 85% (85% modern carbon (pMC)) or more. Specifically, the paper layer (11) may have a biocarbon content of 85% to 100%, 85% to 99%, 85% to 95%, or 90% to 95%. Since the biocarbon content of the paper layer (11) is within the above range, carbon dioxide emission of the laminate (10) can be minimized. Here, the biocarbon content may refer to a value measured according to ASTM D6866.
[0044] The paper layer (11) may have a tensile strength of 8 MPa or more. Specifically, the tensile strength of the paper layer (11) may be 8 MPa to 100 MPa, 20 MPa to 90 MPa, 30 MPa to 80 MPa, 40 MPa to 70 MPa, or 50 MPa to 60 MPa. Since the tensile strength of the paper layer (11) is within the above range, it has the mechanical strength and rigidity required for processing, thereby improving the processability and manufacturing efficiency of the laminate (10). Here, the tensile strength may refer to a value measured according to ASTM D882.
[0045] The paper layer (11) may have a tear strength of 20 gf to 600 gf. Specifically, the tear strength of the paper layer (11) may be 50 gf to 600 gf, 100 gf to 450 gf, 150 gf to 300 gf, 180 gf to 280 gf, or 200 gf to 250 gf. Since the tear strength of the paper layer (11) is within the above range, it is possible to prevent the paper layer (11) from being torn or having poor cuttability during the processing of the laminate (10). In addition, when opening the packaging material obtained from the laminate (10), the packaging material can be well opened without a tool.
[0046] Here, the tear strength may refer to a value measured according to TAPPI method 414om-98.
[0047] The paper layer (11) may have a thickness of 30 g / m 2 Up to 350g / m 2 Specifically, the basis weight of the paper layer (11) can be 50 g / m 2 Up to 330g / m 2 , 100g / m 2 Up to 320g / m 2 , 150g / m 2 Up to 310g / m 2 , 200g / m 2 Up to 300g / m 2 , or 250g / m 2 Up to 290g / m 2 Since the basis weight of the paper layer (11) is within the above range, the mechanical strength of the laminate (10) can be ensured.
[0048] The paper layer (11) may have a thickness of 0.6 g / cm 3 Up to 1.2g / cm 3 Specifically, the density of the paper layer (11) can be 0.7 g / cm 3 Up to 1.2g / cm 3 , 0.8g / cm 3 Up to 1.2g / cm 3 , or 0.9g / cm 3 Up to 1.1g / cm 3 .
[0049] The paper layer (11) may account for 50 wt% or more of the total weight of the laminate (10). Specifically, the content of the paper layer (11) may be 50 wt% to 95 wt%, 55 wt% to 95 wt%, 55 wt% to 85 wt%, 60 wt% to 80 wt%, or 65 wt% to 75 wt%, based on the total weight of the laminate (10). Since the content of the paper layer (11) is within the above range, the laminate (10) can be treated as paper alone, so that the recyclability of the laminate (10) can be excellent.
[0050] In addition, the thickness of the paper layer (11) is 50% or more of the total thickness of the laminate (10). Specifically, it may be 60% or more, 70% or more, 80% or more, or 90% or more (e.g., 30% to 99%, 40% to 99%, 50% to 97%, 60% to 95%, or 70% to 93%). More specifically, the thickness of the paper layer (11) may be 25 μm to 500 μm, 40 μm to 450 μm, 50 μm to 400 μm, 80 μm to 380 μm, or 100 μm to 360 μm.
[0051] Meanwhile, the paper layer (11) may include a functional coating as required. Specifically, if the laminate (10) requires higher barrier properties, heat insulation and high strength, a functional coating may be formed on one or both sides of the paper layer (11), wherein the functional coating is formed from a coating composition, wherein the coating composition comprises a material selected from graphene oxide, clay, montmorillonite, cyclodextrin, nanocellulose, aluminum (Al), cellulose, silicon oxide (SiO x ) and at least one of aluminum oxide (Al2O3).
[0052] In addition, in order to improve the adhesion with the film layer (12) and the gas barrier properties of the laminate (10), the paper layer (11) may further include a primer layer, which is formed by a primer composition containing a water-soluble resin (such as polyvinyl alcohol (PVOH)); or a composition containing at least one of an ethylene-vinyl acetate based resin, a polyurethane based resin and an acryl based resin.
[0053] Film
[0054] The laminate (10) according to an embodiment of the present invention comprises a film layer (12). The film layer (12) is used to enhance the gas barrier property, sealing property and biodegradability of the laminate (10).
[0055] The film layer (12) may contain polyhydroxyalkanoate (PHA). Specifically, the film layer (12) may consist only of polyhydroxyalkanoate (PHA), or may further contain a biodegradable resin in addition to polyhydroxyalkanoate (PHA). The biodegradable resin may specifically be at least one selected from polylactic acid (PLA), polybutylene adipate terephthalate (PBAT), polybutylene succinate (PBS), thermoplastic starch (TPS), polyvinyl alcohol (PVA) and polycaprolactone (PCL). Since the film layer (12) further contains a biodegradable resin while containing polyhydroxyalkanoate (PHA), the biodegradability of the laminate (10) in the ocean and soil can be good because it can be well decomposed by microorganisms. In particular, since the film layer (12) substantially contains polyhydroxyalkanoate (PHA), and polyhydroxyalkanoate (PHA) is decomposed faster by microorganisms, the biodegradation rate of the film layer (12) can also be faster.
[0056] Furthermore, if the goal of reducing carbon dioxide emissions while achieving mechanical properties and biodegradability is desired, the film layer (12) may further comprise at least one of bio-derived polyethylene (bio-PE) and bio-derived polypropylene (bio-PP) in addition to polyhydroxyalkanoate (PHA).
[0057] Specifically, the film layer (12) may contain polyhydroxyalkanoate (PHA) and polylactic acid (PLA). In this case, the weight ratio of polyhydroxyalkanoate (PHA) and polylactic acid (PLA) used in the film layer (12) may be 1:9 to 9:1, specifically 2:8 to 8:2, 2.5:7.5 to 7.5:2.5, 3:7 to 7:3, 3.5:6.5 to 6.5:3.5, or 4:6 to 6:4. When the weight ratio is within the above range, the biodegradability of the laminate (10) can be improved, and the sealing strength and tensile strength of the film layer (12) can also be ensured at the required level.
[0058] The polyhydroxyalkanoate (PHA) used in the film layer (12) may be prepared (synthesized) by a known method using a microorganism, or may be a polyhydroxyalkanoate (PHA) in which the content of the repeating unit derived from the monomer is controlled within a specific range. Specifically, the polyhydroxyalkanoate (PHA) may be a homopolymer obtained by using one monomer as a reactant, or may be a copolymer obtained by using two or more monomers as reactants.
[0059] More specifically, the polyhydroxyalkanoate (PHA) may be a homopolymer or a copolymer: the homopolymer comprises repeating units derived from a monomer selected from 3-hydroxypropionic acid (3HP), 4-hydroxybutyrate (4HB), 3-hydroxyvalerate (3HV), 5-hydroxyvalerate (5HV), 3-hydroxyhexanoate (3HH), 6-hydroxyhexanoate (6HH) and 3-hydroxyoctanoate (3HO); and the copolymer comprises at least one repeating unit (A) derived from a monomer selected from 3-hydroxybutyrate (3HB), 3-hydroxypropionic acid (3HP), 4-hydroxybutyrate (4HB), 3-hydroxyvalerate (3HV), 5-hydroxyvalerate (5HV), 3-hydroxyhexanoate (3HH), 6-hydroxyhexanoate (6HH) and 3-hydroxyoctanoate (3HO).
[0060] If the polyhydroxyalkanoate (PHA) is a copolymer comprising a repeating unit (A), the content of the repeating unit (A) may be 0.1% to 50% by weight (specifically 2% to 45%, 4% to 43%, 6% to 40%, or 8% to 35% by weight), based on the total weight of the polyhydroxyalkanoate (PHA). Since the content of the repeating unit (A) is within the above range, melt extrusion coating and film processing of melting the polymer resin by heat can be performed. That is, if the content of the repeating unit (A) exceeds 50% by weight, the melt strength of the molten resin (PHA resin) will be low, making it difficult to increase the processing speed or to make it into a laminate (laminated film). In addition, if the content of the repeating unit (A) is less than 0.1% by weight, the crystallinity will be too high, making it difficult to achieve the mechanical properties required for the packaging material.
[0061] Specifically, the polyhydroxyalkanoate (PHA) may be a copolymer comprising a first repeating unit (B) and a second repeating unit (C), respectively, wherein the first repeating unit (B) is derived from a monomer selected from 3-hydroxybutyrate (3HB), 3-hydroxypropionic acid (3HP), 4-hydroxybutyrate (4HB), 3-hydroxyvalerate (3HV), 5-hydroxyvalerate (5HV), 3-hydroxyhexanoate (3HH), 6-hydroxyhexanoate (6HH) and 3-hydroxyoctanoate (3HO); and the second repeating unit (C) is derived from a monomer selected from 3-hydroxybutyrate (3HB), 3-hydroxypropionic acid (3HP), 4-hydroxybutyrate (4HB), 3-hydroxyvalerate (3HV), 5-hydroxyvalerate (5HV), 3-hydroxyhexanoate (3HH), 6-hydroxyhexanoate (6HH) and 3-hydroxyoctanoate (3HO), wherein the first repeating unit (B) and the second repeating unit (C) are different from each other.
[0062] If the polyhydroxyalkanoate (PHA) is a copolymer comprising a first repeating unit (B) and a second repeating unit (C), the contents of these repeating units are not particularly limited, but the content of the first repeating unit (B) or the content of the second repeating unit (C) may be 0.1 wt % to 50 wt % (specifically 2 wt % to 45 wt %, 4 wt % to 43 wt %, 6 wt % to 40 wt %, or 8 wt % to 35 wt %) based on the total weight of the polyhydroxyalkanoate (PHA).
[0063] More specifically, the polyhydroxyalkanoate (PHA) may be a copolymer comprising a first repeating unit (D) derived from 3-hydroxybutyrate (3HB) and a second repeating unit (E), wherein the first repeating unit (D) is derived from 3-hydroxybutyrate (3HB); and the second repeating unit (E) is derived from a monomer (comonomer) selected from 3-hydroxypropionic acid (3HP), 4-hydroxybutyrate (4HB), 3-hydroxyvalerate (3HV), 5-hydroxyvalerate (5HV), 3-hydroxyhexanoate (3HH), 6-hydroxyhexanoate (6HH) and 3-hydroxyoctanoate (3HO).
[0064] If the polyhydroxyalkanoate (PHA) is a copolymer comprising a first repeating unit (D) and a second repeating unit (E), the content of these repeating units is not particularly limited, but the content of the second repeating unit (E) can be 0.1% by weight to 50% by weight based on the total weight of the polyhydroxyalkanoate (PHA), and therefore, the content of the first repeating unit (D) can be 50% by weight to 99.9% by weight. Since the contents of the first repeating unit (D) and the second repeating unit (E) are both within the above range, the formability of the laminate can be improved and the mechanical properties required as a packaging material can be ensured. Specifically, based on the total weight of the polyhydroxyalkanoate (PHA), the content of the first repeating unit (D) can be 55% by weight to 98% by weight, 57% by weight to 96% by weight, 60% by weight to 94% by weight, 65% by weight to 92% by weight. In addition, the second repeating unit (E) may be included in an amount of 2 to 45 wt%, 4 to 43 wt%, 6 to 40 wt%, or 8 to 35 wt%, based on the total weight of the polyhydroxyalkanoate (PHA).
[0065] As an example, the polyhydroxyalkanoate (PHA) can be a poly(3-hydroxybutyrate-co-4-hydroxybutyrate) (poly(3HB)-co-(4HB)) copolymer. As another example, the polyhydroxyalkanoate (PHA) can be a poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (poly(3HB)-co-(3HV)) copolymer.
[0066] The average molecular weight of the polyhydroxyalkanoate (PHA) can be 30,000 g / mol to 1,000,000 g / mol, specifically 80,000 g / mol to 900,000 g / mol, 150,000 g / mol to 850,000 g / mol, or 250,000 g / mol to 750,000 g / mol. If the average molecular weight of the polyhydroxyalkanoate (PHA) is less than 30,000 g / mol, the low molecular weight makes it difficult to achieve the required sealing strength and tensile strength when it is processed into a laminate (laminated film), or it is difficult to be used as a packaging material due to the fast degradation rate. In addition, if the average molecular weight of the polyhydroxyalkanoate (PHA) exceeds 1,000,000 g / mol, the viscosity of the molten resin (PHA resin) will be too high and it is difficult to process with an extruder.
[0067] In addition, the melt flow index (MFI) of the polyhydroxyalkanoate (PHA) is 0.1g / 10 minutes to 40g / 10 minutes when measured under the conditions of 165°C and 5kg. Specifically, it can be 0.5g / 10 minutes to 25g / 10 minutes, 1g / 10 minutes to 15g / 10 minutes, or 2g / 10 minutes to 10g / 10 minutes. If the melt flow index of the polyhydroxyalkanoate (PHA) is less than 0.1g / 10 minutes, the viscosity of the molten resin will be too high, making it difficult to extrude and coat, or the shrinkage is too large, thereby deteriorating the processability. In addition, if the melt flow index of the polyhydroxyalkanoate (PHA) exceeds 40g / 10 minutes, the melt strength of the molten resin is too low, and it is difficult to process into a laminate (laminated film).
[0068] The film layer (12) containing polyhydroxyalkanoate (PHA) may further contain a synthetic resin as required. Specifically, when high barrier properties of the laminate (10) are required, the film layer (12) may further contain at least one synthetic resin, such as ethylene vinyl alcohol (EVOH), polyvinyl chloride (PVC) or polyvinylidene chloride (PVDC).
[0069] Meanwhile, the film layer (12) may have a biocarbon content (renewable carbon content (carbon ratio)) of 40% (40% modern carbon (pMC)) or more. Specifically, the film layer (12) may have a biocarbon content of 40% to 100%, 50% to 95%, 60% to 90%, or 70% to 85%. Since the biocarbon content of the film layer (12) is within the above range, carbon dioxide emissions of the laminate (10) can be minimized. Here, the biocarbon content may refer to a value measured according to ASTM D6866.
[0070] The film layer (12) may have a tensile strength of 5 MPa or more. Specifically, the tensile strength of the film layer (12) may be 5 MPa to 120 MPa, 10 MPa to 100 MPa, 15 MPa to 80 MPa, 20 MPa to 70 MPa, or 25 MPa to 60 MPa. Since the tensile strength of the film layer (12) is within the above range, it has the mechanical strength and rigidity required for processing, thereby improving the processability and manufacturing efficiency of the laminate (10). Here, the tensile strength may refer to a value measured according to ASTM D882.
[0071] The film layer (12) may have a sealing strength of 0.5 kgf or more, 0.6 kgf or more, 0.7 kgf or more, 0.8 kgf or more, 0.9 kgf or more, 1.0 kgf or more, 1.1 kgf or more, or 1.2 kgf or more. Specifically, the sealing strength of the film layer (12) may be 0.6 kgf to 5 kgf, 0.6 kgf to 3 kgf, 0.7 kgf to 2.5 kgf, 0.7 kgf to 2 kgf, or 0.8 kgf to 1.5 kgf. Since the sealing strength of the film layer (12) is within the above range, the sealing property of the laminate (10) is ensured, so that the laminate (10) can be used as a packaging material for packaging not only in a short term, but also in a long term. Here, the sealing strength may refer to a value measured according to ASTM D882.
[0072] The film layer (12) may account for less than 50% by weight of the total weight of the laminate (10). Specifically, based on the total weight of the laminate (10), the content of the film layer (12) may be 3% to 49.9% by weight, 5% to 45% by weight, 8% to 40% by weight, 15% to 45% by weight, or 10% to 35% by weight. Since the content of the film layer (12) is within the above range, while ensuring the gas barrier property and sealing property of the laminate (10), the recyclability may be excellent.
[0073] In addition, the thickness of the film layer (12) is less than 75% of the total thickness of the laminate (10). Specifically, it can be 70% or less, 65% or less, 60% or less, 50% or less, 40% or less, or 30% or less (for example, 1% to 70%, 1% to 60%, 3% to 50%, 5% to 40%, or 7% or 30%). Specifically, the thickness of the film layer (12) can be 8μm to 70μm, 10μm to 70μm, 12μm to 55μm, 20μm to 50μm, or 25μm to 45μm. Since the thickness of the film layer (12) is within the above range, the recyclability of the laminate (10) can be excellent, and it has excellent sealing and gas barrier properties.
[0074] The film layer (12) may further include a functional coating as required. Specifically, if the laminate (10) requires higher barrier properties, heat insulation and high strength, a functional coating may be formed on one or both sides of the film layer (12), wherein the functional coating is formed from a coating composition, wherein the coating composition comprises a material selected from aluminum (Al), graphene oxide, clay, montmorillonite, cyclodextrin, nanocellulose, cellulose, silicon oxide (SiO x ) and at least one of aluminum oxide (Al2O3).
[0075] Meanwhile, the laminate (10) according to the embodiment of the present invention may further include an adhesive layer (13) according to the manufacturing method, and the adhesive layer (13) will be referred to as Figure 2 Description is as follows.
[0076] Adhesive layer
[0077] The laminate (10) according to the embodiment of the present invention may further include an adhesive layer (13) for bonding the paper layer (11) and the film layer (12) together. Specifically, the adhesive layer (13) is formed between the paper layer (11) and the film layer (12), thereby playing a role in bonding the paper layer (11) and the film layer (12) together firmly, so as to improve the processability and usability of the laminate (10).
[0078] The adhesive layer (13) may include an adhesive material that can exhibit high adhesive strength without deteriorating the physical properties of the laminate (10). Specifically, the adhesive layer (13) may include at least one adhesive material selected from polyvinyl alcohol (PVA), ethylene-vinyl acetate (EVA) resin, acrylic resin, polyurethane resin, polyolefin resin, polybutylene succinate (PBS), polybutylene adipate terephthalate (PBAT) and polylactic acid (PLA).
[0079] The thickness of the adhesive layer (13) may be 0.5 μm to 25 μm, 0.6 μm to 15 μm, or 0.7 μm to 8 μm. When the thickness of the adhesive layer (13) is within the above range, processability and usability of the laminate (10) may be improved.
[0080] The laminate (10) including the paper layer (11) and the film layer (12) according to the embodiment of the present invention has the above-mentioned optimized physical properties, and has a tensile strength of 15MPa to 150MPa, 20MPa to 130MPa, or 30MPa to 80MPa. Since the tensile strength of the laminate (10) is within the above-mentioned range, the laminate (10) can show better processability.
[0081] The laminate (10) according to the embodiment of the present invention may have a sealing strength of 0.8kgf to 10kgf, 1kgf to 7kgf, or 1.1kgf to 5kgf. Since the sealing strength of the laminate (10) is within the above range, the laminate (10) can be advantageously used as a packaging material in various fields.
[0082] The laminate (10) according to an embodiment of the present invention may have a peel strength (bonding strength between the paper layer (11) and the film layer (12)) of 80 gf or more, 90 gf or more, 100 gf or more, 150 gf or more, or 200 gf or more (specifically, 100 gf to 2,000 gf, 300 gf to 1,000 gf, or 400 gf to 800 gf). Since the peel strength of the laminate (10) is within the above range, the laminate (10) can exhibit better processability. In addition, when the bonding strength between the paper layer (11) and the film layer (12) is high, the peel strength cannot be measured because the paper layer (11) peels off itself. In this case, the peel strength can be the most excellent.
[0083] The oxygen transmission rate of the laminate (10) according to the embodiment of the present invention may be 1 cc / m 2 ·Daily up to 1200cc / m 2 ·day, specifically 1cc / m 2 ·Daily up to 950cc / m 2 ·Day, 1cc / m 2 ·Daily up to 500cc / m 2 ·day, or 1cc / m 2 ·Daily up to 300cc / m 2 ·day. In addition, the water vapor transmission rate of the laminate (10) according to the embodiment of the present invention may be 1 g / m 2 ·Day to 150g / m 2 Day, specifically 1g / m 2 ·Day to 80g / m 2 ·Day, 1g / m 2 ·Day to 50g / m 2 ·day, or 1g / m 2 ·Day to 15g / m 2 Since the oxygen permeability and water vapor permeability of the laminate (10) are both within the above ranges, the laminate (10) can be advantageously used as a packaging material in various fields due to its excellent gas barrier properties.
[0084] In particular, since the laminate (10) according to an embodiment of the present invention includes a paper layer and a film layer having optimized physical properties, even if the laminate (10) does not include a barrier layer containing a metal material or a barrier material (such as EVOH, PVA, PVDC, etc.), its gas barrier properties against oxygen and / or moisture can also be excellent.
[0085] The laminate (10) according to an embodiment of the present invention may have a total biocarbon content (renewable carbon content (carbon ratio)) of 25% (25% modern carbon (pMC)) or more. Specifically, the laminate (10) may have a total biocarbon content of 25% to 100%, 35% to 100%, 50% to 100%, 70% to 100%, or 90% to 100%. Since the total biocarbon content of the laminate (10) is within the above range, the carbon dioxide emission of the laminate is minimized, so that it can be advantageously used as a material for packaging containers or cartons that meet domestic and international carbon emission reduction requirements. Here, the biocarbon content may refer to a value measured according to ASTM D6866.
[0086] The laminate ( 10 ) according to an embodiment of the present invention may have a thickness of 30 μm to 600 μm, 40 μm to 500 μm, 50 μm to 400 μm, or 80 μm to 300 μm.
[0087] Since the laminate (10) according to the embodiment of the present invention includes a paper layer and a film layer having optimized physical properties, it can have tensile strength, sealing strength, peeling strength, etc., thereby being advantageously used as a packaging material for packaging products in various fields. In addition, since it includes a paper layer (11) that can be handled separately and a film layer (12) that has excellent biodegradability in the ocean and soil, and its total biocarbon content is 25% or more, its recyclability and environmental protection can be excellent.
[0088] The method for manufacturing the laminate (10) according to an embodiment of the present invention is not particularly limited, but can be prepared by the following process: applying a resin composition (biodegradable resin composition) for forming a film layer on a paper substrate by resin melt coating (such as extrusion coating, hot melt coating, etc.), or using an adhesive laminating film.
[0089] The resin composition for forming the film layer basically comprises polyhydroxyalkanoate (PHA), and the coating amount thereof can be 8 g / m 2 Up to 70g / m 2 , 15g / m 2 Up to 70g / m 2 , or 25g / m 2 Up to 60g / m 2 Since the coating amount is within the above range, a film layer (12) that satisfies the required gas barrier properties, sealing properties, recyclability, etc. can be formed.
[0090] In addition, when the resin composition for forming the film layer is extrusion coated, the appropriate processing temperature of the extruder may be 140° C. to 240° C., 150° C. to 220° C., or 160° C. to 210° C. Since the processing temperature of the extruder is within the above range, the film layer (12) can be smoothly formed while preventing the polyhydroxyalkanoate (PHA) used in the resin composition for forming the film layer from being degraded.
[0091] Packaging Materials
[0092] The present invention provides a packaging material including a laminate. Specifically, the packaging material according to the embodiment of the present invention can be the laminate itself as described above, or can be a product obtained by adding various functional layers to the laminate and performing post-processing on the laminate.
[0093] The packaging material according to an embodiment of the present invention may further include a surface coating as a functional layer to improve the printability, antifouling and water resistance of the packaging material. The surface coating may include a water-soluble material and have water resistance. As an example, the surface coating may include at least one selected from a thermosetting acrylic resin, a polyurethane resin and a polyhydroxyalkanoate (PHA).
[0094] Since the packaging material according to an embodiment of the present invention includes a surface coating layer and a laminate, it may have a structure of a surface coating layer, a paper layer, and a film layer, wherein an adhesive layer or a primer layer may be interposed between the paper layer and the film layer.
[0095] The packaging material according to the embodiment of the present invention can be used alone to package various articles, and can also be used for packaging after post-processing. Examples of post-processing include a process for combining bubble cloth to increase shock absorption and a process for forming into a desired shape (e.g., extrusion molding, injection molding, compression molding, pressure molding, blow molding or blow molding, thermoforming, etc.).
[0096] Since the packaging material according to an embodiment of the present invention includes a laminate having the above-mentioned paper layer and film layer, it has excellent recyclability and biodegradability, as well as sealing strength, peeling strength and gas barrier properties. Therefore, it can be advantageously used for packaging various articles that require not only short-term sealing properties but also long-term sealing properties, such as food, medicines, cosmetics and industrial products.
[0097] Specifically, the packaging material according to the embodiment of the present invention can be used as a food packaging material such as coffee, cup rice, dried fish, distillate; a mask packaging material; a cosmetic packaging material; a pharmaceutical packaging material; or as a paper packaging material, such as a milk box. As an example, the shape of the packaging material according to the embodiment of the present invention can be a paper container, a double-sided sealed bag, a three-sided sealed bag, an M-sided sealed bag, a box bag (flat bottom bag), a stick bag, etc.
[0098] Mode for the Invention
[0099] Hereinafter, the present invention will be described in detail with reference to Examples, but the scope of the present invention is not limited to the Examples.
[0100] <Preparation of Laminate>
[0101] Example 1
[0102] A resin composition for forming a film layer (PLA:PHA weight ratio of 6:4) comprising polyhydroxyalkanoate (CJ CheilJedang, containing 28 wt% of 4HB repeating units (poly(3HB)-co-(4HB)) and polylactic acid (PLA from NatureWorks) was extrusion coated (extruder temperature was 200°C or less) onto a paper substrate (thickness: 350±15 μm) having a biochar content of 95% or more (95 pMC or more), a tensile strength of 50 MPa, a tear strength of 200 gf, and a basis weight of 280 g / m 2 , to form a film layer with a tensile strength of 25 MPa and a sealing strength of 0.6 kgf (thickness: 40 μm). Laminates with a total biochar content of 96% or more (96 pMC or more) were prepared through the above process. Here, the tensile strength and sealing strength of the paper substrate and the film layer were measured using an Instron 34SC-1 universal testing machine.
[0103] Example 2 to Example 4
[0104] A laminate was prepared in the same manner as in Example 1, except that the physical properties and composition of the paper substrate and the film layer were adjusted as shown in Table 1 below.
[0105] Comparative Example 1 to Comparative Example 6
[0106] A laminate was prepared in the same manner as in Example 1, except that the physical properties and compositions of the paper substrate and the film layer were adjusted as shown in Table 2. Here, poly(3-hydroxybutyrate) (poly(3HB)) was used as PHA in the film layer of Comparative Example 1.
[0107] [Table 1]
[0108]
[0109] [Table 2]
[0110]
[0111] <Test Example>
[0112] Test Example 1: Processability of packaging materials
[0113] In order to determine whether it can be processed into packaging materials, it is checked whether the resin composition (biodegradable resin) used to form the film layer can be extruded to form a layer, and whether the laminate can be processed by printing, slitting and bagging. Specifically, in the case of extruding to form a layer, the possibility of the resin composition forming a film layer, the amount of gel in the film layer, and the possibility of forming a thickness that can be used as a packaging material are evaluated. For laminates, it is evaluated whether the laminate is damaged during the processing of printing, slitting and bagging, and whether there are defects caused by shrinkage or poor cutting.
[0114] If the evaluation result was passed, it was rated as ○. If it was unsatisfactory due to physical properties, it was rated as ×. The results are shown in Table 3 below.
[0115] Test Example 2: Seal Strength
[0116] The seal strength of the laminate was measured using an Instron 34SC-1 universal testing machine with a sample width of 15 mm, a measuring length of 30 mm, and a measuring speed of 200 mm / min.
[0117] When the measured seal strength was 0.8 kgf or more, it was rated as ○. When less than 0.8 kgf, it was rated as ×. The results are shown in Table 3 below.
[0118] Test Example 3: Peel Strength
[0119] The peel strength between the paper layer and the film layer of the laminate was measured using an Instron 34SC-1 universal testing machine with a sample width of 15 mm, a measuring length of 30 mm, and a measuring speed of 200 mm / min.
[0120] When the measured peel strength was 200 gf or more, or if the adhesive strength between the paper layer and the film layer was strong, causing the paper layer to break and peel off, and the peel strength could not be measured, it was rated as ○. When it was less than 200 gf, it was rated as ×. The results are shown in Table 3 below.
[0121] Test Example 4: Gas Barrier Properties
[0122] The water vapor transmission rate (WVTR) of the laminate was measured at 38±0.5°C and 90±2% relative humidity using a Mocon Permatran-w3 / 33 water vapor transmission rate meter. In addition, the oxygen transmission rate (OTR) of the laminate was measured at 23±0.5°C using a Mocon OX2-TRAN 2 / 12 oxygen transmission rate meter.
[0123] When the measured oxygen transmission rate is 1,200cc / m 2 days or less, water vapor transmission rate is 150g / m 2 · days or less, it is rated as ○. When the measured oxygen permeability exceeds 1,200cc / m 2 · days and the water vapor transmission rate exceeds 150g / m 2 The results are shown in Table 3 below.
[0124] [Table 3]
[0125]
[0126] Referring to Table 3, the laminates according to Examples 1 to 4 of the present invention have a highly recyclable paper layer and a biodegradable film layer (containing no components such as petrochemical synthetic resins and aluminum), so they can be processed separately and have excellent environmental friendliness while ensuring the processability, sealing strength, peel strength and gas barrier properties required as packaging materials.
[0127] In contrast, in the laminates of Comparative Examples 1 to 6, they cannot form a film by themselves (Comparative Example 3), or even after extrusion coating the resin composition for forming a film layer on a paper substrate, their physical properties are very low, so it is difficult to process them into packaging materials or use them for packaging food, cosmetics, etc.
[0128] These results support the fact that when manufacturing a laminate comprising a paper layer and a film layer, it is necessary to optimize the biocarbon content and physical properties of each of the paper layer and the film layer, as described in the present invention.
[0129] [Explanation of Reference Numerals]
[0130] 10: Laminate
[0131] 11: Paper layer
[0132] 12: Film layer
[0133] 13: Adhesive layer
Claims
1. A laminate comprising a paper layer and a film layer, wherein: The paper layer has a biochar content of 85% or more and a tensile strength of 8 MPa or more, The film layer comprises polyhydroxyalkanoate (PHA) and has a thickness of 8 μm to 70 μm, The polyhydroxyalkanoate (PHA) is a homopolymer or copolymer: the homopolymer comprises repeating units derived from a monomer selected from 3-hydroxypropionic acid (3HP), 4-hydroxybutyrate (4HB), 3-hydroxyvalerate (3HV), 5-hydroxyvalerate (5HV), 3-hydroxyhexanoate (3HH), 6-hydroxyhexanoate (6HH) and 3-hydroxyoctanoate (3HO); the copolymer comprises at least one repeating unit derived from a monomer selected from 3-hydroxybutyrate (3HB), 3-hydroxypropionic acid (3HP), 4-hydroxybutyrate (4HB), 3-hydroxyvalerate (3HV), 5-hydroxyvalerate (5HV), 3-hydroxyhexanoate (3HH), 6-hydroxyhexanoate (6HH) and 3-hydroxyoctanoate (3HO), and the at least one repeating unit is used in an amount of 0.1 wt% to 50 wt%, and The thickness of the film layer is less than 75% of the total thickness of the laminate.
2. The laminate according to claim 1, wherein The polyhydroxyalkanoate (PHA) is a copolymer comprising a first repeating unit and a second repeating unit, wherein the first repeating unit and the second repeating unit are respectively derived from a monomer selected from 3-hydroxybutyrate (3HB), 3-hydroxypropionic acid (3HP), 4-hydroxybutyrate (4HB), 3-hydroxyvalerate (3HV), 5-hydroxyvalerate (5HV), 3-hydroxyhexanoate (3HH), 6-hydroxyhexanoate (6HH) and 3-hydroxyoctanoate (3HO), and the first repeating unit and the second repeating unit are different from each other.
3. The laminate according to claim 2, wherein: The polyhydroxyalkanoate (PHA) is a copolymer comprising 0.1 wt % to 50 wt % of the first repeating unit or the second repeating unit, based on the total weight of the polyhydroxyalkanoate (PHA).
4. The laminate according to claim 2, wherein: The polyhydroxyalkanoate (PHA) is a copolymer comprising 50 wt % to 99.9 wt % of a first repeating unit derived from 3-hydroxybutyrate (3HB) and 0.1 wt % to 50 wt % of a second repeating unit derived from a monomer selected from 3-hydroxypropionic acid (3HP), 4-hydroxybutyrate (4HB), 3-hydroxyvalerate (3HV), 5-hydroxyvalerate (5HV), 3-hydroxyhexanoate (3HH), 6-hydroxyhexanoate (6HH) and 3-hydroxyoctanoate (3HO).
5. The laminate according to claim 1, wherein The film layer has a biochar content of 40% or more.
6. The laminate according to claim 1, wherein: The laminate has a 1 cc / m 2 ·Daily up to 1,200cc / m 2 ·Day oxygen transmission rate and 1g / m 2 ·Day to 150g / m 2 Water vapor transmission rate of the day.
7. The laminate according to claim 1, wherein: The film layer has a tensile strength of 5 MPa or more and a sealing strength of 0.5 kgf or more.
8. The laminate according to claim 1, wherein: The film layer further comprises at least one selected from polylactic acid (PLA), polybutylene adipate terephthalate (PBAT), polybutylene succinate (PBS), thermoplastic starch (TPS), polyvinyl alcohol (PVA), polycaprolactone (PCL), bio-derived polyethylene and bio-derived polypropylene.
9. The laminate according to claim 1, wherein: The polyhydroxyalkanoate (PHA) is a poly(3-hydroxybutyrate-co-4-hydroxybutyrate) copolymer.
10. The laminate according to claim 1, wherein: The polyhydroxyalkanoate (PHA) has an average molecular weight of 30,000 g / mol to 1,000,000 g / mol.
11. The laminate according to claim 1, wherein: The paper layer has a tensile strength of 8MPa to 100MPa, a tear strength of 20gf to 600gf, and a 2 Up to 350g / m 2 The basis weight.
12. The laminate according to claim 1, wherein: The laminate has a peel strength of 200 gf or more.
13. The laminate according to claim 1, wherein: The laminate has a total biocarbon content of 25% or more.
14. A packaging material comprising the laminate according to any one of claims 1 to 13.
Citation Information
Patent Citations
Biodegradable packaging, preparation method thereof, security pack and security method of mobile device
KR102404216B1
Display apparatus including the thermal spreading shee
KR102500214B1
Multilayer body and use of same
WO2021100732A1
PHA composition and method for manufacturing same
WO2022086229A1
KR20220029920A